Wizerunek Czecha w »Zrób sobie raj« czy może kreowanie nowych stereotypów - Szczepańska, Elżbieta (Komisja Slawistyczna PAN, Oddział w Poznaniu, IFS UAM, Wydawnictwo PRO, 2013)
The article concerns the Czech and Polish stereotypes in the book of M. Szczygieł Zrób sobie raj. In his essays Szczygieł presents well known and the mostly negative images from new and more positive positions. Such a biased vision of the Czech raises the question of whether the picture is close to reality, and how much it is still a stereotype.

, ,
Keywords: Czech; nation; styereotype; creation of reality